Peningkatkan Keterampilan Pasing Bawah dalam Permainan Bola Voli Melalui Aktivitas Fisik - Rahiman; Mariyamah, Siti; Maryani, Tri (Universitas PGRI Pontianak, 2024)
Volleyball is a game sport played by two opposing groups. Each group has six players. The principle of playing volleyball is to play the ball with divolley (hit with the limbs) and try to drop the ball into the opponent's field by crossing the ball over the net and keeping the ball from falling on its own field. Even though volleyball is a team game, mastering basic techniques individually is absolutely necessary. This means that in coaching in the early stages it is necessary to emphasize mastering the basic techniques of the game, one of which is the basic passing technique. To achieve high performance, it is necessary to have a good and regular physical training program to improve the bottom passing skills. Forms of physical exercise that can be applied include lifting barbells and push-ups, which aim to increase the strength of the arm and abdominal muscles of a player/student, thereby influencing the results of the match. The main problem in this research is; Is there an increase in lower passing skills in volleyball games through barbell lifting and push-up exercises for male students of class VI SD Negeri 01 Sukadana 2022/2023? Based on the existing problems, the purpose of this research is; to improve lower passing skills in volleyball games through barbell lifting and push-up exercises for male students of grade VI SD Negeri 01 Sukadana